ND ISOTOPE COMPOSITION AND RARE EARTH ELEMENT DISTRIBUTION IN EARLY PALEOZOIC BIOGENIC APATITE FROM BALTOSCANDIA: A SIGNATURE OF IAPETUS OCEAN WATER - Felitsyn S.; Sturesson U.; Holmer L.; Popov L. (My University, 1998)
Analyses of the Nd isotopic composition and REE distribution in biogenic apatite (organophosphatic brachiopods and conodont elements) from the Cambrian and Ordovician sequences of the Baltic plate give new insights into the development of the southeastern segment of the continental margin bounding the Iapetus ocean. The Nd isotope analyses show εNd(t) of ˜-8.0 for the Cambrian, indicating that the main source of the sedimentary deposition came from weathered sedimentary rocks of Vendian and Cambrian age. The increase of εNd(t) to ˜-5.0 for the Early Ordovician indicates the appearance of a new source of radiogenic Nd in the surrounding area---most likely a volcanic arc along the western borderland of Baltic plate from Arenigian time. Samples of Cambrian biogenic apatite show significantly lower total amounts of REE than do the Ordovician samples, and this is probably due to a shorter exposure to seawater before burial during Ordovician sedimentary accumulation in Baltoscandia. These preliminary results suggest that biogenic apatite from the Baltoscandian basin preserves geochemical signatures of the water masses that will be important for understanding the evolution of the Iapetus ocean during the early Paleozoic.
Keywords: Paleozoic; Paleozoic; Палеозой